2015
DOI: 10.1371/journal.pone.0135933
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Parameters of Malnutrition and Diagnostic Measures of Sarcopenia in Geriatric Outpatients

Abstract: ObjectivesDiagnostic criteria for sarcopenia include measures of muscle mass, muscle strength and physical performance. Consensus on the definition of sarcopenia has not been reached yet. To improve insight into the most clinically valid definition of sarcopenia, this study aimed to compare the association between parameters of malnutrition, as a risk factor in sarcopenia, and diagnostic measures of sarcopenia in geriatric outpatients.Material and MethodsThis study is based on data from a cross-sectional study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 44 publications
9
41
0
Order By: Relevance
“…SGA identified malnutrition in 41% of the patients with most of them being considered moderately malnourished. Those findings were consistent with recent studies on this issue (9,17,18,21) . Furthermore, these results clearly shows that patients assessed in a ward setting present more frequent and severe malnutrition whatever the tool used to assess nutritional status.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…SGA identified malnutrition in 41% of the patients with most of them being considered moderately malnourished. Those findings were consistent with recent studies on this issue (9,17,18,21) . Furthermore, these results clearly shows that patients assessed in a ward setting present more frequent and severe malnutrition whatever the tool used to assess nutritional status.…”
Section: Discussionsupporting
confidence: 94%
“…Several reported studies have shown that functional status defined by handgrip strength correlates with severity of malnutrition and clinical outcome in different disease states (9,17,18,21) . More than a half of the tested patients in this sample displayed deficient/ low values in dynamometry, which was associated with the high prevalence of PCM detected in CLD patients as it was previously reported (4,8,13,14,19,23,27) .…”
Section: Discussionmentioning
confidence: 99%
“…Parameters of malnutrition were found to be associated with both relative and absolute muscle mass in geriatric outpatients [11]. The etiology of malnutrition in older patients is usually multifactorial and includes reduced nutritional intake and metabolic effects of illness [9].…”
Section: Introductionmentioning
confidence: 99%
“…Being underweight is associated with poor nutritional status, sarcopenia and related weakness of respiratory muscles, and frailty [1618]. Such factors could adversely influence outcomes after major lung resection, as has been recently shown [8, 13].…”
mentioning
confidence: 99%